EVALUASI PELAKSANAAN PEMBELAJARAN KIMIA SMA KURIKULUM 2013 - Dian Sri Suhesti (Ideguru: Jurnal Karya Ilmiah Guru, 2019)
The aims of this study were: (1) to recognize the implementation of chemistry learning. (2) to identify the assessment conducted by the teacher in chemistry learning process. This study was an evaluation study with formative approach from Scriven. Evaluation was performed in chemistry learning process. The study was conducted at SMA N 1 Banguntapan (Senior High School). The respondents were 58 students. The instruments of the study was questionnaires with sumative rating scale models that modify the Likert scale. Data analysis techniques was quantitative descriptive, analyzed by using excel program thus was presented in the histogram to illustrate the achievement of the learning process and assessment conducted by the teacher. The results of this study were: (1) the achievement of the chemistry learning process was divided into 3 stages: the preliminary sections indicated a good category (pronounced by 55.17% respondents), the learning model revealed a good category as well (pronounced by 51.73% respondents) and the practicum indicated the very good category (pronounced by 55.17% respondents); (2) the learning assessment conducted by the teacher was in the good category, (pronounced by 65.52% respondents). Overall evaluation results show that the chemistry learning done by the teacher was good.